VERBAL AND NON VERBAL SIGN ON "SAMSUNG GALAXY’S: GROWING UP” AUDIOVISUAL ADVERTISEMENT - Ni Nyoman Yudianti; Ketut Artawa; Yana Qomariana (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Abstract: The purpose of the analysis is to find out the meaning of the verbal and visual signs (signifiers) used in the advertisement and the messages it contained. In the analysis, the main theory that is used is the theory of Semiotic by Ferdinand de Saussure. This theory is applied for the main step of the analysis, to figure out the signifieds of these signifiers. The supporting theories are the theory of verbal and the non-verbal aspect in advertisement which proposed by Gillian Dyer which is applied for the first step in the analysis - to find out the appropriate verbal and visual signs in the advertisement which are then being withdrawn into the main analysis. The finding of this study is that this advertisement uses the verbal aspects which had been categorized into: brand name, slogan and jingle, key words, uses of imperative, intentional omission, formula, and absence of language. The non-verbal signs used are categorized into: age, gender, national and racial, body, prop, and setting. The verbal and visual signs are correlated to form the meanings and real messages of the advertisement. The prominent meaning of the advertisement is that Samsung Galaxy is the best smartphone ever.